2012
DOI: 10.1021/jp307221q
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Lithium in Bulk Amorphous Silicon: A Theoretical Study

Abstract: The rate performance of lithium-ion secondary batteries depends critically on the kinetic transport of Li within the anode material. Here we use first-principles theoretical calculations to study the diffusion of Li in the low-concentration limit, using model electrodes of crystalline and four-fold coordinated bulk amorphous silicon. We identify Li diffusion pathways that have relatively low energy barriers (<0.50 eV) in amorphous silicon and discuss how diffusion at short (∼2.5 Å), intermediate (∼10 Å), and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
140
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 35 publications
16
140
0
1
Order By: Relevance
“…The diffusivity value of Li in Si-based electrode materials has been investigated using experimental methods and computer simulations. [26][27][28][29][30][31][32][33][34][35] The local environments and dynamics of lithium ions in the binary lithium silicide were studied using NMR technique 36,37 . Kuhn et al 37 found that nine of thirteen crystallographically independent Li sites in the Li 12 Si 7 take part in an extreme fast long-range diffusion process characterized by an activation energy of only 0.18 eV in the Li 12 Si 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The diffusivity value of Li in Si-based electrode materials has been investigated using experimental methods and computer simulations. [26][27][28][29][30][31][32][33][34][35] The local environments and dynamics of lithium ions in the binary lithium silicide were studied using NMR technique 36,37 . Kuhn et al 37 found that nine of thirteen crystallographically independent Li sites in the Li 12 Si 7 take part in an extreme fast long-range diffusion process characterized by an activation energy of only 0.18 eV in the Li 12 Si 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The values ranged from -2.68 to 8.15 eV, with a standard deviation of 3.40 eV. The Cs, which is an impurity with a relatively larger size than those studied in the similar amorphous systems 46,47,51,[60][61][62][63] , turned out to be highly stable as interstitials in the a-SiC. The high stability of Cs defects vs. bulk is possibly due to the large relaxations available to the a-SiC system, analogous to the observation of Ag defects in the HEGB 24 , although the detailed mechanism of stabilizing Cs interstitials in a-SiC was not explicitly investigated here.…”
Section: Ab-initio Calculationsmentioning
confidence: 96%
“…This can be seen by comparing the insertion energies of Refs. [20,67], where default basis sets of the Spanish Initiative for Electronic Simulations with Thousands of Atoms (SIESTA) program were used, with those of Ref. [14], where bases tuned in this way were used, as well as with available plane wave results [12,59,60].…”
Section: Interactions Of LI Na K and Mg With Monoelemental Group Imentioning
confidence: 99%
“…The rationale behind using an amorphous structure is two-fold: firstly, an amorphous structure may have larger-volume insertion sites, which would lead to lower strain energy; secondly, a metastable amorphous structure is expected to be more reactive towards Li, leading to a lower (stronger) E b . We used a previously published [67] amorphous Si (a-Si) structure. An amorphous structure has multiple insertion sites with different E b , and we found that many of those sites had E b much lower than that of c-Si; this is shown in Figure 1.…”
Section: Interactions Of LI Na K and Mg With Monoelemental Group Imentioning
confidence: 99%